Job insecurity and salary in the Spanish hotel sector: a regional analysis - García-Pozo, Alejandro; López-Rubio, José; Sánchez-Ollero, José Luis (My University, 2014)
The economic crisis in which the Spanish economy finds itself has had serious negative impact on wages and in the lack of job stability for Spanish workers. In this paper, using the data available from the sample of 2010 of the Spanish Wage Structure Survey (WSS), we estimate the return to human capital in the hotel sector for the main Spanish touristic regions. For this purpose has been estimated an expanded version of the Mincer (1974) wage equation which includes, in addition to variables related to formal education, work experience and tenure, other variables that attempt to measure the effects on salary of workers' personal characteristics and the features of the job. Regarding the descriptive results obtained from the sample, these indicate that the gross salary per hour worked by hotels' employees are much lower than the salary of the workers in other services; in addition to this, the average years of schooling completed by hotels' employees is also much lower in comparison to the average of the workers of other privates services sectors of the Spanish economy. The estimates calculated for each region show that in the hotel sector the return to human capital, and in particular the return to formal education, are much lower than those estimation made to the workers of other private services sectors. In addition, other highlight factor is that, comparing with the data of the WSS-2006, the fact of having a full-time permanent contract has less influence on the salary of hotels employees in the regions of Andalusia, Canary Islands and Balearic Islands. Finally, our estimates show that wage discrimination based on gender is much more pronounced in other private services of the tourist regions analyzed than in the hotel sector, reaching in the first case and in the Balearic Islands on 23.57 % to the detriment of women compared to men. As main conclusion, the results obtained in this study show the precarious labor conditions of hotels workers even in regions where tourism has a relevant role in their economy.
Keywords: Hostelería - Personal - España; Gender; Job insecurity; Hotel; Salary